The Future of Wild Mammals in Oil Palm Landscapes in the Neotropics - Payán, Esteban; Boron, Valeria (Frontiers in Forests and Global Change, 2019)
Colombia is the fourth largest producer of palm oil in the world with a growth of 42% in 2017, affecting its ecosystems and biodiversity. Here we review current understanding from science, policy, and practice to help shape a better fate for mammals across oil palm landscapes in Colombia. In order to prevent large mammal species erosion and decimation as has happened in South East Asia, the following lessons in zoning, infrastructure, harvest, monitoring and research should be implemented. Native habitat is irreplaceable. New oil palm frontiers should occur in degraded ecosystems, with adequate governance and without requirement of new infrastructure. Roads favor hunting, logging, and disorganized human occupation. Plantations should conserve water bodies and forests to ensure connectivity and refuge for sensitive mammal species. Higher structural complexity with added plants is desired for a varied mammal assemblage. Harvest should be done manually and crepuscular work hours should be avoided. Application of the abovementioned tactics will consolidate a more sustainable strategy for the future of mammals in oil palm landscapes in mega-diverse countries.